2007
DOI: 10.4049/jimmunol.179.1.229
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor Cross-Talk: Exposure to Lipopolysaccharide Induces an Alternate Pathway for B Cell Receptor-Induced ERK Phosphorylation and NF-κB Activation

Abstract: BCR signaling in naive B cells depends on the function of signalosome mediators; however, prior engagement of CD40 or of IL-4R produces an alternate signaling pathway in which Bruton’s tyrosine kinase, PI3K, phospholipase Cγ2, and protein kinase Cβ are no longer required for BCR-induced downstream events. To explore the range of mediators capable of producing such an alternate pathway for BCR signaling, we examined the TLR4 agonist, LPS. B cell treatment with LPS at relatively low doses altered subsequent BCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…To examine whether, like DPP4 [7] , DPP8 and DPP9 are upregulated upon lymphocyte activation, mouse splenocytes were stimulated in vitro with PWM [43][44][45] and LPS [46,47] . DPP8 and DPP9 mRNA was markedly upregulated in PWM stimulated mouse splenocytes in a time dependent manner (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether, like DPP4 [7] , DPP8 and DPP9 are upregulated upon lymphocyte activation, mouse splenocytes were stimulated in vitro with PWM [43][44][45] and LPS [46,47] . DPP8 and DPP9 mRNA was markedly upregulated in PWM stimulated mouse splenocytes in a time dependent manner (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…However, this observation still does not eliminate the possibility of a role for Btk downstream of TACI because others have previously shown that anti-IgM-induced B cell proliferation can be restored in XID mice in the presence of second signals such as CD40L, LPS, and CpG through a mechanism called "receptor cross-talk" (53)(54)(55). According to Guo et al (56), in addition to the signalosome-dependent (classical) pathway, a signalosome-independent (alternative) pathway is activated by second signals (such as CpG) in BCR-stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stimulation of B cells with sCD40L, IL-4, and LPS reprograms the BCR signaling pathway, enhancing ERK activation and bypassing the requirement for phosphatidylinositol 3-kinase (PI3-K) [82][83][84][85][86]. The findings that only B cells chronically exposed to self-antigen are susceptible to repression by IL-6 and sCD40L suggests that chronic BCR-derived signals "reprogram" the outcome of IL-6R and CD40 signal transduction.…”
Section: Arresting and Silencing Sm-specific B Cellsmentioning
confidence: 92%